THE ROLE OF FOOD ENRICHED WITH ῶ-3 POLYUNSATURATED FATTY ACIDS IN CHILDREN’S NUTRITION - T.N. Stepanova; V.A. Skvortsova; T.E. Borovik; N.N. Semenova; O.L. Lukoyanova (Вопросы современной педиатрии)
The article describes a structure and functions of long-chain polyunsaturated fatty acids (PUFA) and their role in infants’ nutrition. It was marked that Russian market has only one product for additional food enriched with PUFA ῶ-3 for children from 4 months old. It is milkless buckwheat «Heinz».Key words: children, nutrition, additional food, long-chain polyunsaturated fatty acids.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):169-173)